Dance in the Christian tradition - Yarber, Angela (Review and expositor, 2024)
Dance is a kinesthetic form of story-telling. Although in many Baptist circles dance has been prohibited, this article examines the edifying role of dance in scripture, theology, and Christian history and in personal experience. Dance is most evocative and meaningful when it empowers those who have previously never used their bodies as a conduit for worship or whose gender or sexuality has been excluded from worship leadership.